Identity Of The Self In Paul Ricœur: Between grammatical preference and practical choice - Correia, Mário (Sofia, 2025)
This article does not address the notion of narrative identity, which dominates practically all and any research on the subject by this author, and rightly so, since this is a key notion in this regard. However, our path takes us on other paths, although they converge on narrative identity. We open up a field in which we can see different ways of approaching the theme of identity in Paul Ricœur, using grammatical and practical preferences as a reference point. At the end of the path, we aim to further broaden the horizon of the theme of the identity of the self, including pointing to the continuity of the reflection.